PROSEDUR ATAS PENCATATAN KAS KECIL PADA PT ANDOR JINSOM KHARISMA - Yollanda Arthamevia, (2023)
Petty cash has an important role in the company's operational activities. Usually used in small transactions that occur every day starting from the company's operating hours until the end of operating hours. Petty cash is an asset in meeting the company's needs to carry out its operational activities with the simplest procedures. In its management, petty cash is carried out by the finance and accounting divisions who have the skills and expertise, as well as the importance of providing understanding to employees on matters relating to the procedures for using petty cash funds so that misuse, fraud and theft can be avoided.